Productivity Breakthrough With TPM : A Case Study - Khai Huat, Jeffrey Low (2003)
This paper focuses on a study of Total Productive Maintenance (TPM) implementation in a business segment in Infineon Technologies (M) Sdn, Bhd where it contributed significantly on improving the productivity of a bottleneck process in its production line.